Understanding Employee Relations / A Behavioural Approach - Rollinson Derek (Amacom, 1993)
This comprehensive textbook gives an integrated and fresh treatment of employee relations at the organizational level. List of Figure and Tables, Introduction, An Introduction to Employee Relations, The Individual and Workgroups, Collective Organizations of Employees, Management in Employee Relations, The State in Employee Relations, Discipline and Grievance, Communications in Employee Relations, Involvement and Participation, Collective Bargaining, Negotiation, Industrial Action, Management Initiatives, Policy and Strategy in Employee Relations, References, Author and Subject Index.